Integrating Land Change Science and Savanna Fire Models in West Africa - Paul Laris (Land, 2013)
Fire is a key component of many land use systems and a determinant of land change. There is a growing concern that climate change will cause more catastrophic fires, but in many areas the impacts will be mediated by human land use practices. In African savannas, for example, fires are frequent and research finds low inter-annual variability in burned areas in places with highly variable rainfall. This regularity of fire suggests that African regimes are humanized, meaning that they are governed by human practices more than climate variation. Although these fire regimes are stable, they vary greatly over space. This paper will determine the reasons for two distinctly different fire regimes in Mali by integrating land change and savanna fire science. The study takes a two pronged approach to examine the causes of fire regimes and the reasons they change. It tests the notion that land cover (not land use) governs fire regimes by combining long term burn scar and vegetation analysis with local interviews. Results indicate that efforts to link fire and land change science, need to focus more on subtle differences in land cover, landscape pattern and human practices, than on drought, land use or fire policy.